2020
DOI: 10.1093/jaocint/qsz013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the 3M™ Petrifilm™ Rapid E. coli/Coliform Count Plate for the Enumeration of E. coli and Coliforms: Collaborative Study, First Action: 2018.13

Abstract: Background The 3M™ Petrifilm™ Rapid E. coli/Coliform Count Plate is a selective and differential sample-ready-culture medium designed for the rapid enumeration of Escherichia coli (E. coli) and coliforms in the food and beverage industries. Objective The 3M Petrifilm Rapid E. coli/Coliform Count Plate was compared to the U.S. Food and Drug Administration Bacteriological Analytical Manual (BAM) Chapter 4 Enumeration of Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Other coliforms can also be detected on Petrifilm, under the form of red colonies. Validation tests previously demonstrated that this method did not produce results significantly different from those obtained using method ISO 16649-2:2017 (Bird et al, 2020).…”
Section: Sampling and Microbiological Analysesmentioning
confidence: 89%
“…Other coliforms can also be detected on Petrifilm, under the form of red colonies. Validation tests previously demonstrated that this method did not produce results significantly different from those obtained using method ISO 16649-2:2017 (Bird et al, 2020).…”
Section: Sampling and Microbiological Analysesmentioning
confidence: 89%
“…Total coliform bacteria and fecal coliform bacteria were quantified by Most Probable Number (MPN) test. In addition, the microbiological analysis investigated for the presence of Escherichia coli (E. coli) and coliform bacteria using membrane filtration with 3M Petrifilm TM for E. coli/coliform count (EC) (Bird et al 2020). All analytical methods were performed according to the standard methods for the examination of water and wastewater (Public Health Act 1992; Eugene et al 2012).…”
Section: Water Quality Analysesmentioning
confidence: 99%
“…The fecal content was pooled then examined at the Veterinary Diagnostic Laboratory Faculty of Veterinary Medicine Khon Kaen University, Thailand. A coliform/escherichia coli test was performed using the 3M Petrifilm Rapid E.coli/coliform counting plate, which was validated according to the AOAC Validation Guidelines following the AOAC Official Method of Analysis SM process [17]. A fecal sample was diluted with sterile saline peptone water in ratios ranging from 10:1 to 10:10, and the solutions were mixed thoroughly with a vortex mixer.…”
Section: Microbial Contamination On Fecal Mattermentioning
confidence: 99%